KEMITRAAN MASYARAKAT BERSAMA KELOMPOK PENDAMPING ANAK AUTIS DI KOTA MALANG - Hariyani, Sri; Sari, Eva (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
Cognitive problems in children with autism involve teaching materials. Textbooks for autis children use the 2013 curriculum reference. In learning, teachers do not have special worksheets for autis children. The teacher uses textbooks for elementary school students. The teacher must copy the sheets in the textbook to be taught to autis children. Of course this is not effective and efficient. The implementation of this community service program is intended to help resolve partner issues. Servants deliver solutions to partners. The solution is in the form of providing learning materials for Student Worksheets that are appropriate to the cognitive needs of autis children. Worksheets contains a color drawing design to help facilitate the understanding of autis children. The combination of images and colors is intended to attract the attention of autis children, so autis children want to provide themselves for learning. This method of community service is carried out using collaborative methods with mentors. Implementation methods include preparation, implementation and evaluation of activities. In the preparation stage, the servant coordinates with the companion about the design of the student Worksheet. During the implementation phase, the servants with mentor joint compile the Student Worksheet. Servants carry out product validation to find out the level of feasibility. Furthermore, the service performs a trial using the Student Worksheet. The trial was carried out by observing the effectiveness and efficiency of the use of Student Worksheets in learning by a mentor. In the evaluation phase of the program implementation, the servant receives input and advice from the mentor to improve the Student Worksheet. Student Worksheets make it easy for facilitators to teach students.